Sistemas de medição fasorial sincronizada: aplicações na recomposição do sistema elétrico de potência - Andre Fernandes Coelho Rezende Santos (2010)
This master thesis investigates the impact of the Synchronized Phasor Measurement Systems on the Power System Restoration process. The viability of current and voltage phase angle measurement brings a significant improvement for electrical system restoration. One of the most complex actions during power system restoration is the closure of breakers between two electrical islands due to the lack of real time information to support operators during the decision making process. Synchronized Phasor Measurement System can disposal those information. With the objective to contribute to the researches related to phasor measurement applications in power system operation,mainly with respect to system restoration, this work presents a basic text about this subject. The actual scenario of power system restoration proceedings and the utilization of phasor measurement in this process are discussed. Finally, this work includes specific proposals related to the practical implementation of these measurements in a real powersystem.